Case Report: Biological treatment of epidermolysis bullosa acquisita: report on four cases and literature review - Konrad Szymański; Cezary Kowalewski; Ewelina Pietrzyk; Katarzyna Woźniak (Frontiers in Immunology, 2023)
Epidermolysis bullosa acquisita (EBA) is a chronic, recurrent autoimmune subepidermal bullous disease characterized by the presence of autoantibodies targeting type VII collagen -- basement membrane zone antigen. Standard therapy for EBA includes a combination of systemic corticosteroids and dapsone; however, severe cases may require advanced treatment. The current article reports on four EBA cases in which biologics: infliximab, rituximab (Rtx), and intravenous immunoglobulin (IVIG) were applied. All patients fulfilled the clinical and immunological criteria of EBA: they presented tense blisters healing with atrophic scars on the skin on traumatized areas and in mucous membranes. The diagnosis of EBA was established using numerous techniques: direct and indirect immunofluorescence, salt split skin, ELISA, Fluorescence Overlay Antigen Mapping using Laser Scanning Confocal Microscopy. Since all the patients did not achieve long-term remission on standard treatment (prednisone, dapsone) due to ineffectiveness or side effects of drugs, they eventually were treated with biologics leading to extraordinary skin improvement and stopping the disease for 1-3 years. Biologics in all patients were tolerated very well. No side effects were observed during application as well as multi-month follow-up. The presented cases provide a premise that biological drugs can be a valuable component of EBA therapy.